2021
DOI: 10.1002/cssc.202100129
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Interfacial Oxygen‐Bridge Chemical Bonding in Core‐Shell Transition Metal Phosphides/Carbon Hybrid Boosting Oxygen Evolution Reaction

Abstract: A designed structure which CoP nanoparticles (NPs) ingeniously connected with graphene-like carbon layer via in-situ generated interfacial oxygen-bridge chemical bonding was achieved by a mild phosphorization treatment. The results proved that the presence of phosphorus vacancies is a crucial factor enabling formation of CoÀ OÀ C bonds. The direct coupling of edge Co of CoP with the oxygen from functional groups on the carbon layer was proposed. As a catalyst for electrocatalytic water splitting, the manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…Similarly, due to the peeling of CNT during argon etching, the peak of CO becomes less obvious. The chemical bond of M–O–C, detected in both C 1s and O 1s spectra, can accelerate the electron transfer and improve the catalytic kinetic speed according to previous reports …”
Section: Results and Discussionsupporting
confidence: 62%
“…Similarly, due to the peeling of CNT during argon etching, the peak of CO becomes less obvious. The chemical bond of M–O–C, detected in both C 1s and O 1s spectra, can accelerate the electron transfer and improve the catalytic kinetic speed according to previous reports …”
Section: Results and Discussionsupporting
confidence: 62%
“…Many reports exhibited that various derivatives of 1 st -row transition metal-based catalysts like sulphides, phosphides, selenides, hydroxides and oxides are reported to be most effective for OER and HER. 18–29 Recently, some reports showed that transition metal-based LDHs are effective for both OER and HER because of their unique layered structure in various electrolyte medium. 18–29 So far, many bimetallic transition metal-based layered double hydroxide (LDH) materials such NiFe-LDH, CoFe-LDH, CoNi-LDH, CoMn-LDH, and NiV-LDH have been reported widely as catalysts for water splitting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…18–29 Recently, some reports showed that transition metal-based LDHs are effective for both OER and HER because of their unique layered structure in various electrolyte medium. 18–29 So far, many bimetallic transition metal-based layered double hydroxide (LDH) materials such NiFe-LDH, CoFe-LDH, CoNi-LDH, CoMn-LDH, and NiV-LDH have been reported widely as catalysts for water splitting reaction. 30–40 Some of them showed excellent OER and HER activity in various pH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various transition-based metal oxides, hydroxides, LDHs, chalcogenides, phosphides and nitride-based materials have attracted much attention from researcher due to their fascinating electrocatalytic activity and unique stability, irrespective of the medium used as the electrolyte. 14–19 However, although numerous reports are available on these transition metal derivatives for the OER and HER with good stability, owing to their low conductivity, especially transition metal-based oxides, LDH, hydroxides and oxyhydroxides, their application towards the large-scale production of hydrogen still a challenge. 4 Thus, to overcome this issue, researchers focused on the modification of the above-mentioned materials by adopting various strategies such as the incorporation of foreign cations or anions, creation of vacancies and enhancing the conductivity of electrocatalyst materials by using various conductive supports such as nickel foam (NF), copper foam (CF) and graphene-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…4 Thus, to overcome this issue, researchers focused on the modification of the above-mentioned materials by adopting various strategies such as the incorporation of foreign cations or anions, creation of vacancies and enhancing the conductivity of electrocatalyst materials by using various conductive supports such as nickel foam (NF), copper foam (CF) and graphene-based materials. 19–23 Among them, the use of graphene-based composites with transition metal-based derivatives has attracted significant attention not only for the fabrication of excellent water splitting electrocatalysts but also materials for other electrochemical applications such as batteries, sensors, and supercapacitor applications. 24–29 Graphene with a conjugated hexagonal lattice and fascinating two-dimensional nanosheet-like structure, has attracted significant attention for the preparation of energy storage and conversion devices owing to its huge surface to volume ratio, great electrical conductivity and high electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%